Peran Orang Tua Kristen Dalam Mengantisipasi Tantangan Perilaku Ateis Praktis Bagi Keluarga - Eki Yanto Neonisa; Yakobus Adi Saingo (Institut Teknologi dan Bisnis (ITB) Semarang, 2025)
The rapidly developing and dynamic modern era has also presented various ideologies and behaviors that have caused many people to begin to doubt the existence of God in the universe. This condition also has its own influence on Christian families whose children no longer have high enthusiasm in efforts to strengthen their spirituality, so that practical atheistic behavior or attitudes that no longer view religion and spirituality as important elements in human life often emerge. The purpose of this study is to analyze the role of Christian parents in anticipating practical atheistic behavior for the family. The research method applied is literature study and analysis by reduction. The research results explain, Parents have an important role and responsibility in the family, including having awareness in seeking education in such a way as to strengthen the spirituality of each family member to be obedient and believe in God. The example of parents who consistently embody their faith through their daily behavior in the family can encourage children to imitate it without feeling burdened/forced. Christian parents must be able to create a family whose character is in accordance with Christian values, so that it cannot be influenced by heretical ideologies and practical atheistic behavior.